Peramalan Penerimaan Pajak Kendaraan Bermotor Menggunakan Metode Triple Exponential Smoothing di Sumatera Utara - Dewi, Ratna Sri; Jaya, Indra; Husein, Ismail (Universitas Cokroaminoto Palopo, 2024)
At this time, motorized vehicles have become a primary need. Therefore, it is necessary to take into account revenues for motor vehicle taxes so that the government has a good motor vehicle tax calculation produce is one aspect of revenue management that is very helpful in achieving the goals set by the government. Therefore, it is necessary to estimate motor vehicle tax revenues correctly so that it can be seen how much revenue will be managed properly. The purpose of this research is to get the forecast value of motor vehicle tax revenue for the next year with a low MAPE. The method used is the Triple Exponential Smoothing method with a constant alpha = 0,3 and obtains a MAPE of less than 10 % which means it is very good. The results of this study there are several districts / cities that experienced a decrease in motor vehicle tax revanues.